Estimation of dietary intake of sodium, potassium, phosphorus and protein in healthy Indian population and patients with chronic kidney disease - Kaur, Prabhjot; Yadav, Ashok Kumar; Pal, Arnab; Jassal, Ravjit Singh; Shafiq, Nusrat; Sahni, Nancy; Kumar, Vivek; Jha, Vivekanand (Frontiers in Nutrition, 2024)
Poor nutritious diet is a major risk element for non-communicable diseases, which are of considerable public health concern. Given the diverse dietary patterns in India, precise determination of nutrient consumption is crucial for disease management. The present study assessed the dietary intake of sodium, potassium, protein, and phosphorus among North Indians. This cross-sectional study included healthy adults and adults with stage 2 to 4 chronic kidney disease (CKD). We analysed sodium, protein, potassium and phosphorus intakes using one-time 24-hour urinary excretion. We also evaluated the performance of various equations available to estimate sodium intake using a spot urine sample with respect to the sodium excretion measured in a 24-hour urine sample. A total of 404 subjects (182 adult healthy subjects and 222 adults with CKD), with a mean age of 47.01±11.46 years were studied. Mean dietary intakes of sodium, salt, potassium, protein and phosphorus were 2.94±1.68 g/day, 7.42±4.24 g/day, 1.43±0.59 g/day, 47.67±14.73 g/day and 0.86±0.39 g/day, respectively. Consumption of sodium, salt, protein, potassium, and phosphorus among healthy population vs those with CKD were 2.81±1.60 vs 3.05±1.73 g/day (p=0.152), 7.08±4.04 vs 7.70±4.37 g/day (p=0.143), 47.16±14.59 vs 48.08±14.86 g/day (p=0.532), 1.38±0.59 vs 1.48±0.58 g/day (p=0.087) and 0.86±0.41 vs 0.87±0.37 g/day (p=0.738), respectively. Men had higher consumption of these nutrients than women. Compared to non-hypertensives, hypertensive subjects had higher consumption of salt (8.23 ± 4.89 vs 6.84 ± 3.59 g/day, p=0.002) and potassium (1.51 ± 0.63 vs 1.38 ± 0.55 g/day, p=0.024), however, no difference were found in protein and phosphorus intakes. In terms of performance of equations used to estimate 24-h sodium intake from spot urinary sodium concentration against the measured 24-h urinary sodium excretion, INTERSALT 2 equation exhibited the least bias [1.08 (95% CI, -5.50 to 7.66)]. The study shows higher-than-recommended salt and lower-than-recommended potassium intake in the north Indian population compared to those recommended by guidelines such as KDIGO. The dietary protein intake is below the recommended dietary allowance. These findings help the development of targeted policies for dietary modification to reduce the risk of the development and progression of CKD.